The Influence of Tradisional Games Ma’danda and Ma’boy on Gross Motor Skills of Early Childhood Children in TK ABA Boronguntia and TK Julukanaya in Bajeng District - Sidiq, Nurul Jamiah (PT ARRUS Intelektual Indonesia, 2024)
This research discusses the lack of gross motor skills in early childhood. The study aims to examine how the implementation of the tradisional game Ma’danda in ABA Boronguntia Kindergarden and ma’boy in Julukanaya Kindergarden can improve children’s gross motor skills. The research subjects were 14 children in Group B of ABA Boronguntia Kindergarden and 14 children in Group B of Julukanaya Kindergarden. The type of research is an experimental methode using Quasi Eksperiment with a Non-Equivalent Control Group Desain. Data analysis was conducted using descriptive analysis with SPSS 22 for windows. The research result have been carried out through several meetings and based on the discussion and analysis that have been carried out. It is concluded that children’s gross motor skills in the Ma’danda game, as evidenced by the post-test result in ABA Boronguntia Kndergarden showing 1 child in the high category (11,2%) and 13 children in very high category (92,8%). Meanwhile, the post-test result in Julukanaya Kindergarden showed 2 children in very high category (14,3%), and 12 children in the high category (85,7%).